Heavy mineral resource potential of Tista river sands, Northern Bangladesh. Issue 3 (3rd July 2018) - Biswas, P. K.; Ahmed, S. S.; Pownceby, M. I.; Haque, N.; Alam, S.; Zaman, M. N.; Rahman, M. A.
ABSTRACT: Surface and borehole sampling along a ∼80 km section of the lower Tista river, northwestern Bangladesh, indicated that the river sands offer significant potential as a heavy mineral (HM) resource. Characterisation of sediments from the surface to 15 m depth showed that the sand-sized component was dominated by quartz, feldspar, mica, lithic fragments, amphibole and pyroxene group minerals. The most common particle size was between +125–500 μm with 84 wt-% of all material reporting to this size range. Laterally spaced sampling indicated slight grain size coarsening upstream. Heavy liquid separation studies revealed that HMs such as amphiboles, micas, garnets, aluminosilicate (Al2SiO5) phases, ilmenite and zircon made up ∼10.99% (on average). The percentage of valuable HMs (ilmenite, rutile, zircon, monazite, garnet) was 2.47% (average). Detailed borehole sampling and resource mapping of a large, mid-channel sand bar showed that placer-style HM accumulations occur upstream and along the margins of the bar.